A simplified and cost-effective enrichment protocol for the isolation of Campylobacter spp. from retail broiler meat without microaerobic incubation - Zhou, Ping; Hussain, Syeda K.; Liles, Mark R.; Arias, Covadonga R.; Backert, Steffen; Kieninger, Jessica; Oyarzabal, Omar A. (BMC Microbiology, 2011)
Background: To simplify the methodology for the isolation of Campylobacter spp. from retail broiler meat, we evaluated 108 samples (breasts and thighs) using an unpaired sample design. The enrichment broths were incubated under aerobic conditions (subsamples A) and for comparison under microaerobic conditions (subsamples M) as recommended by current reference protocols. Sensors were used to measure the dissolved oxygen (DO) in the broth and the percentage of oxygen (O2) in the head space of the bags used for enrichment. Campylobacter isolates were identified with multiplex PCR assays and typed using pulsed-field gel electrophoresis (PFGE). Ribosomal intergenic spacer analyses (RISA) and denaturing gradient gel electrophoresis (DGGE) were used to study the bacterial communities of subsamples M and A after 48 h enrichment. Results: The number of Campylobacter positive subsamples were similar for A and M when all samples were combined (P = 0.81) and when samples were analyzed by product (breast: P = 0.75; thigh: P = 1.00). Oxygen sensors showed that DO values in the broth were around 6 ppm and O2values in the head space were 14-16% throughout incubation. PFGE demonstrated high genomic similarity of isolates in the majority of the samples in which isolates were obtained from subsamples A and M. RISA and DGGE results showed a large variability in the bacterial populations that could be attributed to sample-to-sample variations and not enrichment conditions (aerobic or microaerobic). These data also suggested that current sampling protocols are not optimized to determine the true number of Campylobacter positive samples in retail boiler meat. Conclusions: Decreased DO in enrichment broths is naturally achieved. This simplified, cost-effective enrichment protocol with aerobic incubation could be incorporated into reference methods for the isolation of Campylobacter spp. from retail broiler meat. © 2011 Zhou et al; licensee BioMed Central Ltd.
Created from Fastlane, Scopus look-up